Clinical and metabolic characteristics of Turkish adolescents with polycystic ovary syndrome. (17th February 2018) - Ates, Seda; Aydın, Serdar; Ozcan, Pinar; Soyman, Zeynep; Gokmen Karasu, Ayse Filiz; Sevket, Osman
Abstract: The aim of this study was to investigate the clinical, endocrine, metabolic features and prevalence of metabolic syndrome (MBS) in Turkish adolescents with polycystic ovary syndrome (PCOS) and the differences in metabolic parameters between adolescent PCOS with or without the presence of polycystic ovaries (PCO) on ultrasound. Subjects ( n = 77) were classified into two groups: oligomenorrhea (O) and clinical and/or biochemical hyperandrogenism (HA) ( n = 38), without PCO and O + HA with PCO ( n = 39). The control group consisted of 33 age-matched adolescents. Adolescents with PCOS had a significantly higher body mass index (BMI), waist circumference and levels of LH, LH/FSH ratio, triglyceride, insulin, HOMA-IR, free androgen index and lower levels of SHBG and FSH. After adjustment for BMI, LH, LH: FSH ratio remained significantly higher. Adolescents with PCOS had a higher prevalence of MBS. No significant differences in lipid profiles, insulin levels and insulin sensitivity in both the PCOS groups were seen. HDL-C levels were lower in the O + HA + PCO group compared to the controls. BMI may be the major contributing factor in the development of metabolic abnormalities in adolescents with PCOS. Impact statement: Many studies have investigated the effect of PCOS on metabolic and cardiovascular risks. It is thought that PCOS increases metabolic and cardiovascular risks. Increase in metabolic and cardiovascular risks associated with PCOS may be handled with early diagnosis and early intervention of PCOS in adolescents, although the diagnosis of PCOS in adolescents could be hard because of the features of PCOS overlapping normal pubertal physiological events. However, early identification of adolescent girls with PCOS may provide opportunities for prevention of well-known health risks associated with this syndrome and reduction of long-term health consequences of PCOS by reducing androgen levels and improving metabolic profile. Our results also support that BMI may be the major contributing factor in the development of metabolic abnormalities in adolescents with PCOS.